Mitigating Dissent: A Grounded Formal Theory of Two Hidden Routines from Corporate Social Irresponsibility to Corporate Social Responsibility - Chen, Zhili (2013)
The study of Corporate Social Responsibility (CSR) has exhausted its primary analytic framework based on corporate social performance, stakeholder theory and business ethics, and needs to re-orient its centre from business to society. Given this direction, a formal grounded theory is adopted to embrace a pluralistic perspective in the research. Instead of trying to fix the definition responsibility and irresponsibility, this paper captures the dynamics of the ir/responsible continuum and tries to build a model which reveals the mechanism underlying the change from irresponsibility to responsibility. Keywords: